Applications of photo-oxidation with 1O2 in multistep reactions - Wu, L.Q. (2019)
There is an increasing drive to perform chemical synthesis in a greener and more environmentally friendly way, particularly on an industrial scale. Usually, this can be achieved by designing new routes to higher value chemicals, by using low hazardous solvents and avoiding the emission of high quantities of waste in an existing process. This Thesis mainly describes the progress towards the applications of dense carbon dioxide as a solvent for conducting the continuous flow reaction with photochemically generated singlet oxygen in a multistep synthesis process. This method helps to achieve a green and efficient way to produce versatile chemicals on a relatively large scale to meet the demand for the production of personalised pharmaceuticals.